Design and Develop a Web-Based Inventory Documentation Information System At CV HOOKAH CROWN - Susanto, Ferdy; Sudarsono, Bernadus Gunawan; Sharyanto, Sharyanto (Journal of Engineering, Technology and Computing (JETCom), 2024)
The current development of information systems and information technology has led to the creation of technological tools that can assist in completing tasks more easily. As a result, many companies now utilize technology to facilitate their operations, such as in managing inventory documents. The purpose of developing this web-based document management information system is to provide convenience for companies in the process of data collection, document storage, inventory calculation, and report generation. Based on the research and discussion, the implementation of this web-based document management system ensures that sales transactions, stock calculations, and report generation are systematically organized, leading to better storage and organization of sales data.